Pengaruh Mekanisme Tata Kelola Perusahaan Terhadap Pengungkapan Islamic Financial Social Reporting (Ifsr) Pada Bank Syariah Di Indonesia - Maulidya Wulandari; Vanica Serly (Jurnal Eksplorasi Akuntansi, 2019)
This study was conducted to determine the effect of independent commissioners and directors on the disclosure of Islamic Financial Reporting (IFSR). Research on Islamic Financial Social Reporting (IFSR) can be said is a fairly recent research finding from a copy of research on ISR, GCG, and financial disclosure. For research in Indonesia, no research has been found that addresses the disclosure of IFSR in Islamic Banks. The IFSR is an index that covers all aspects of financial disclosure, governance, and Islamic social responsibility. The population of this study is Islamic banking in Indonesia, amounting to 12 banks which published annual reports from 2014-2018. Data collection method in this research is documentation study. Analysis of the data used is descriptive statistics, classic assumption tests, and for hypotheses using multiple linear regression analysis. The results of this study indicate that the number of independent commissioners and the number of directors has a positive effect on the disclosure of Islamic Financial Social Reporting (IFSR)